Risk Evaluation of Pathogenic Intestinal Protozoa Infection Among Laboratory Macaques, Animal Facility Workers, and Nearby Villagers From One Health Perspective - Li, Jian; Ren, Yijing; Chen, Haiying; Huang, Weiyi; Feng, Xinyu; Hu, Wei (Frontiers in Veterinary Science, 2021)
Background: Previous epidemiological studies have confirmed non-human primates (NHPs) as reservoirs for Cryptosporidium spp., Giardia intestinalis, and Enterocytozoon bieneusi. It highlights the possibility of interspecies transmission between humans and macaques in laboratory animal facilities. This study aimed to investigate the prevalence of pathogenic intestinal protozoan infections in macaques and humans and to determine the risk of cross-species transmission from One Health view. Materials and Methods: A total of 360 fecal samples, including 310 from the four Macaca mulatta groups, 25 from the facility workers in a laboratory animal facility, and 25 from the villagers nearby in Yongfu country, southeast China, were collected. Nested PCR assays were done for detecting protozoan pathogens from all the specimens. Furthermore, potential risk factors (gender, age and direct contact) on the occurrence of intestinal protozoa infection among different sub group were evaluated. The phylogenetic and haplotype networks analysis was conducted to examine the genetic structure and shared patterns of E. bieneusi and C. cayetanensis. Results: The pathogenic intestinal protozoa were detected in both human and macaque fecal samples. There was no significant difference in four intestinal protozoa infections between facility workers and villagers (2 =2.4, P > 0.05). However, the positive rate of pathogenic intestinal protozoa in the facility workers, who had direct contact with macaques, was significantly higher (OR = 0.31, 95% CI: 0.09 - 1.00, P < 0.05). Thirty-three ITS genotypes of E. bieneusi were identified, including five known genotypes (PigEBITS7, Peru8, Henan V, D, and CM1) and six novel genotypes (MEB1-6). Seven haplotypes were identified in the network analysis from C. cayetanensis positive samples. Meanwhile, phylogenetic and haplotypes analysis confirmed the presence of zoonotic subtypes in NHPs and humans. Conclusion: The data collected from this study confirmed a high prevalence of intestinal protozoan infection in humans and macaques. These results warrant workers of such facilities and residents to limit contact with infected animals in order to minimize related health risks. The need for comprehensive strategies to mitigate the risk of zoonotic transmission, especially from a One Health perspective, is recommended.